Plasticity and Aesthetic Identity; or, Why We Need a Spinozist Aesthetics - Sparrow, Tom (The Nordic Journal of Aesthetics, 2011)
<!–StartFragment–> This essay defends the view that, as embodied, our identities are necessarily dependent on the aesthetic environment. Toward this end, it examines the renewal of the concept of sensation (aisthesis) in phenomenology, but then concludes that the methodology and metaphysics of phenomenology must be abandoned in favor of an ontology that sees corporeal identity as generated by the materiality of aesthetic relations. It is suggested that such an ontology is available in the work of Spinoza, which helps break down the natural/ artificial and human/nonhuman distinctions, and can thereby engender an environmental ethics grounded in aesthetic relations. An explication of body/ world dependence is provided via the concept of plasticity and a properly Spinozist aesthetics is invoked, but remains to be worked out. <!–EndFragment–>